Gdzie te dzieci? O pronatalistycznej (nie)efektywności programu "Rodzina 500 plus" = Where are the children? On the pronatalistic (non)effectiveness of the "Family 500 plus" programme - Kaźmierczak-Kałużna, Izabela (Zielona Góra: Lubuskie Towarzystwo Naukowe)
For three decades, the fertility rate in Poland has been below the level of simple replacement of generations, and long-term demographic forecasts do not indicate any immediate improvement in this respect. The measures taken in recent years as part of a pro-family policy have proved to be ine?ective. This also applies to the "Family 500+" programme introduced in 2016. After an initial increase noted between 2016 and 2017, the fertility rate dropped again.
Keywords: dzietność; wskaźnik dzietności; Program "Rodzina 500+"; polityka prorodzinna; drugie przejście demogra?czne; fertility; fertility rate; "Family 500+" programme; pro-family policy; second demographic transition